Psychoanalytic treatment: a neurobiological view - Elie Cheniaux (Psychology & Neuroscience, 2011)
We present a review of several hypotheses concerning the possible neurobiological correlates of the main processes involved in analytic therapy. Attachment theory may represent an interesting link between psychoanalysis and neurobiology. According to Bowlby's conception, interactions with parental figures during infancy lead to the formation of an "internal working model." This determines how the individual will relate with others and cope with stress throughout life. The patterns formed are in many cases pathological. The internal working model is stored as implicit memory, which is expressed independently of consciousness. Clinical improvement in analytic therapy ultimately depends on changes in the implicit memory system, which entails structural brain modifications. Implicit memory system changes may be related to alterations in explicit memory systems, which result from interpretative work. They may also occur directly as a result of the emotional experiences in the patient-analyst relationship.